Pandemic Disease and Systems Theory. An Ecological View - Stan Amaladas; Ray Becvar (Murmurations, 2020)
The fundamental problem that we raise and address in this paper is the problem of understanding our relationship with our afflictions in ways that are uniquely shaped by such afflictions. We capture our need to shifting our attention from our dominant Western epistemology to systems thinking. In this article, we argue that systems theory and thinking